A STUDY ON DEVELOPMENT OF WOMEN ENTREPRENEURS IN TIRUNELVELI DISTRICT - U, Sangeetha; P. Santhanam; R. Ezhil Jasmine (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Entrepreneurship plays an imperative role for the growth of our economy. It emerges from an individual’s creative spirit into long-term business ownership, employment creation, capital formation and economic security. Entrepreneurial skills are essential for industrialization and for alleviation of mass unemployment and poverty. As technology speeds up lives, women are an emerging economic force, which cannot be neglected by the policy makers. The world’s modern democratic economy depends on the participation of both sexes. Entrepreneurship is an economic activity which is undertaken by an individual or group of individuals. It can be defined as the making of a “new combination” of already existing materials and forces; that entrepreneurship throws up as innovations, as opposed to inventions and that no one is entrepreneur for ever, only when he or she is actually doing the innovative activity.